Nanoparticle exposure and hazard in the ceramic industry: an overview of potential sources, toxicity and health effects - Bessa, M.J. (2020)
The ceramic industry is an industrial sector of great impact in the global economy that has been benefiting from advances in materials and processing technologies. Ceramic manufacturing has a strong potential for airborne particle formation and emission, namely of ultrafine particles (UFP) and nanoparticles (NP), meaning that workers of those industries are at risk of potential exposure to these particles. At present, little is known on the impact of engineered nanoparticles (ENP) on the environment and human health and no established Occupational Exposure Limits (OEL) or specific regulations to airborne nanoparticles (ANP) exposure exist raising concerns about the possible consequences of such exposure. In this paper, we provide an overview of the current knowledge on occupational exposure to NP in the ceramic industry and their impact on human health. Possible sources and exposure scenarios, a summary of the existing methods for evaluation and monitoring of ANP in the workplace environment and proposed Nano Reference Values (NRV) for different classes of NP are presented. Case studies on occupational exposure to ANP generated at different stages of the ceramic manufacturing process are described. Finally, the toxicological potential of intentional and unintentional ANP that have been identified in the ceramic industry workplace environment is discussed based on the existing evidence from in vitro and in vivo inhalation toxicity studies.